Malignant pleural effusion: From diagnostics to therapeutics. - Asciak, R; Rahman, N (Elsevier, 2017)
Malignant pleural effusion is a common complication of cancer and denotes a poor prognosis. It usually presents with dyspnea and a unilateral large pleural effusion. Thoracic computed tomography scans and ultrasound are helpful in distinguishing malignant from benign effusions. Pleural fluid cytology is diagnostic in about 60% of cases. In cytology-negative disease, pleural biopsies are helpful. Current management is palliative. Previously, first-line treatment for recurrent symptomatic malignant pleural effusion was chest drain insertion and talc pleurodesis, with indwelling pleural catheter insertion reserved for patients with trapped lung or failed talc pleurodesis. However, catheter insertion is an increasingly acceptable first-line treatment.